Effect of Heparin and Gelatin Binding Buffalo Seminal Plasma Proteins on Sperm-Egg Binding Assay - ARANGASAMY, A; SINGH, L P; CHAUHAN, M S (The Indian Journal of Animal Reproduction, 2023)
Effect of heparin and gelatin binding buffalo seminal plasma proteins were assessed on fertility status of buffalo cauda spermatozoa by sperm-zona pellucida binding test The results showed difference between protein treated and control groups in the relative number rjf sperm cells bound to the zona pellucida of a batch of in vitro matured buffalo oocytes. These differences suggest a relationship between the sperm-zona pellucida binding capacity and the fertility related semi al plasma proteins.